2020
DOI: 10.1002/cbin.11436
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TTN‐AS1/miR‐134‐5p/PAK3 axis regulates the radiosensitivity of human large intestine cancer cells through the P21 pathway and AKT/GSK‐3β/β‐catenin pathway

Abstract: Radiotherapy is an important adjuvant treatment for large intestine cancer even though it does not cause any response in many patients. The present study aimed to investigate the effects of the TTN antisense RNA 1 (TTN-AS1) long noncoding RNA (lncRNA) on radiotherapy dynamics of large intestine cancer cells and to explore the underlying molecular mechanisms. TTN-AS1 expression was evaluated by reversetranscription quantitative polymerase chain reaction, western blot, and cellular immunofluorescence, and flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…26 Decreasing the expression of miR-134-5p was also suggested to promote radioresistance by the P21 and AKT/ GSK-3β/β-catenin pathway. 27 In our study, the predicted genes targeted by miR-134-5p included ATM and JAK1, both of which have been associated with NPC. Several studies have revealed that ATM mediates DNA repair and activates the resistance of NPC cells to radiotherapy or chemotherapy by the ATM-associated signaling pathway.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…26 Decreasing the expression of miR-134-5p was also suggested to promote radioresistance by the P21 and AKT/ GSK-3β/β-catenin pathway. 27 In our study, the predicted genes targeted by miR-134-5p included ATM and JAK1, both of which have been associated with NPC. Several studies have revealed that ATM mediates DNA repair and activates the resistance of NPC cells to radiotherapy or chemotherapy by the ATM-associated signaling pathway.…”
Section: Discussionmentioning
confidence: 65%
“…miR‐134‐5p potentially acts as a tumor suppressor, repressing the proliferation of NPC cells by directly targeting E74‐like ETS transcription factor 2 (ELF2) 26 . Decreasing the expression of miR‐134‐5p was also suggested to promote radioresistance by the P21 and AKT/GSK‐3β/β‐catenin pathway 27 . In our study, the predicted genes targeted by miR‐134‐5p included ATM and JAK1 , both of which have been associated with NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with our study, these results showed that Dcr3 may be an important molecule in the regulation of radioresistance of lung cancer cells. Numerous studies have suggested the involvement of AKT/GSK-3β pathway in radioresistance [35][36][37][38]. Using the AKT inhibitor MK-2206, we revealed that the inhibition of AKT/GSK-3β pathway was responsible for the effect of OMT on radiosensitivity.…”
Section: P R E P R I N Tmentioning
confidence: 79%
“…Moreover, Chen et al [30] demonstrated that exosomal miR-590-3p derived from cancer-associated fibroblasts (CAFs) increases the radiation resistance of RC by positively regulating the chloride channel accessory 4-dependent PI3K/AKT signaling pathway in vivo and in vitro. Another study showed that, in vitro, the lncRNA, TTN antisense RNA 1, promotes the radiotherapy resistance of CRC cells by negatively regulating miR-134-5p and increasing the expression levels of p21-activated kinase 3, [31] which may be associated with the P21 and AKT/glycogen synthase kinase-3β/β-catenin pathways.…”
Section: Mirnas Affect the Response To Rc Radiotherapy By Regulating ...mentioning
confidence: 99%